Clinico-Epidemiological Study of Management of Blunt Trauma Chest in a Tertiary Center - Dr.G.Kiran; Dr.P.Madan; Dr.Neerajakshi Reddi, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Blunt chest trauma denotes injuries to the chest resulting from forceful impact in the absence of penetration, such as those sustained from a blow, fall, or collision. Chest trauma is the leading cause of death from physical trauma after head and spinal cord injury. Thoracic injuries are primary or a contributing cause of about one- fourth of all trauma-related deaths. The mortality rate in these cases is about 10%. Thoracic injuries account approximately 20–25% of deaths due to trauma. 16,000 deaths occur per year in India alone as a result of chest trauma. Objective: To understand the epidemiological profile of patients reporting to the trauma center of our hospital with blunt thoracic trauma and to ascertain the impact of various etiologies of blunt chest trauma. Materials and methods: Between January 2023 and April 2024, consecutive patients with blunt thoracic trauma, who presented to the emergency department at Rangaraya Medical College (Kakinada, Andhra pradesh, India), were reviewed in this retrospective study. Data collected regarding common injury modes, age and gender distribution, pre-hospitalization practices, clinical presentations, associated injuries, severity of injuries, and management options from the hospital record section and these data were analyzed with descriptive statistics. Results: Majority of the patients were males who were involved in RTA. Presentation was mostly in the form of rib fractures, hemothorax, pneumothorax and flail chest. Most of the patients could be managed conservatively or by inserting an ICD tube and supportive treatment. None required an operative intervention. Mortality was mostly seen only when other systems were involved (CNS, abdominal organs, long bone fractures, spine injuries). Conclusion: Chest injury is seen commonly in RTA patients. Most of the patients of chest injuries can be managed by symptomatic care and simple life-saving intervention, i.e. intercostal drainage. CT chest is better than chest x-ray in early identification of pneumothorax and must be done if available. With increased RTAs, it is needed to have public awareness regarding road safety measures and educating them about the first aid measures for trauma patients.